KEBIJAKAN KEPALA SEKOLAH SD NEGERI DAN SMP NEGERI DALAM PEREKRUTAN TENAGA GURU HONORER DITINJAU DARI PASAL 8 PERATURAN PEMERINTAH NOMOR 48 TAHUN 2005 TENTANG PENGANGKATAN TENAGA HONORER MENJADI CALON PEGAWAI NEGERI SIPIL (Studi Di Kecamatan Jagoi Babang Kabupaten Bengkayang) - NPM. A2021161061, SUNARTO, SH (Jurnal NESTOR Magister Hukum, 2018)
ABSTRAKÂ Tesis ini berjudul â€œKebijakan Kepala Sekolah SD Negeri dan SMP Negeri Dalam Perekrutan Tenaga Guru Honorer Ditinjau Dari Pasal 8 Peraturan Pemerintah Nomor 48 Tahun 2005 Tentang Pengangkatan Tenaga Honorer Menjadi Calon Pegawai Negeri Sipil (Studi di Kecamatan Jagoi Babang Kabupaten Bengkayang)â€. Adapun tujuan dari penelitian ini adalah untuk mengungkapkan dan menganalisis dapat/tidaknya kebijakan Kepala Sekolah SD Negeri dan SMP Negeri dalam penyediaan Tenaga Guru Honorer dipertanggungjawabkan secara hukum dan sikap Dinas Pendidikan dan Kebudayaan Kabupaten Bengkayang terhadap kebijakan Kepala Sekolah SD Negeri dan SMP Negeri dalam perekrutan Tenaga Guru Honorer. Melalui studi kepustakaan dengan menggunakan metode pendekatan hukum empiris diperoleh kesimpulan, kebijakan yang dilakukan oleh Kepala Sekolah SD Negeri dan SMP Negeri di Kecamatan Jagoi Babang Kabupaten Bengkayang dalam hal perekrutan Tenaga Guru Honorer atau Guru Tidak Tetap memang tidak dapat dipertanggungjawabkan secara hukum karena menyalahi ketentuan Pasal 8 Peraturan Pemerintah Nomor 48 Tahun 2005 tentang Pengangkatan Tenaga Honorer Menjadi Calon Pegawai Negeri Sipil. Adapun sikap Dinas Pendidikan dan Kebudayaan Kabupaten Bengkayang terhadap kebijakan yang dilakukan oleh Kepala Sekolah SD Negeri dan SMP Negeri di Kecamatan Jagoi Babang Kabupaten Bengkayang dalam hal perekrutan Tenaga Guru Honorer atau Guru Tidak Tetap adalah menyetujui kebijakan yang dilakukan oleh Kepala Sekolah SD Negeri dan SMP Negeri dalam hal perekrutan Tenaga Guru Honorer atau Guru Tidak Tetap dan memberikan kewenangan kepada Kepala Sekolah SD Negeri dan SMP Negeri di Kecamatan Jagoi Babang Kabupaten Bengkayang untuk merekrut Tenaga Guru Honorer atau Guru Tidak Tetap disebabkan karena memang kondisinya SD Negeri dan SMP Negeri di Kecamatan Jagoi Babang Kabupaten Bengkayang kekurangan tenaga guru, jadi mau tidak mau solusinya dengan merekrut Tenaga Guru Honorer atau Guru Tidak Tetap agar dapat menunjang proses belajar mengajar.Â Kata Kunci : Kebijakan, Perekrutan, Tenaga Guru Honorer. Â Â ABSTRACTÂ This thesis entitled "The Principal Policy of Elementary School and Junior High School in Recruiting Teachers of Honorary Teachers Judging From Article 8 of Government Regulation Number 48 Year 2005 About Appointment of Honorary Staff to Candidate of Civil Servant (Study in Jagoi Babang Sub-district of Bengkayang Regency)". The purpose of this study is to reveal and analyze the can / not the policy of Elementary School and Junior High School principals in the provision of Honorary Teachers are accounted for by the law and attitude of the Education and Culture Office of Bengkayang Regency towards the policy of Elementary School and Junior High School Principal in recruitment of Honorary Teachers. Through literature study using empirical legal approach method, it is concluded that the policy made by the Principal of Elementary School and Junior High School in Jagoi Babang Sub-district of Bengkayang Regency in the case of recruitment of Honorary Teachers or Non-Permanent Teachers can not be legally justified for violating the provisions of Article 8 Government Regulation Number 48 Year 2005 regarding the Appointment of Honorary Personnel Becoming Candidate for Civil Servant. The attitude of the Department of Education and Culture of Bengkayang Regency on the policy made by the Principal of Elementary School and Junior High School in Jagoi Babang Sub-district of Bengkayang Regency in the case of recruitment of Honorary Teachers or Non-Permanent Teachers is to approve the policy made by Principal of Elementary School and Junior High School District Jagoi Babang Bengkayang District in terms of recruitment of Teachers Honorary or Teachers Not Stay and give authority to the Principal of Elementary School and State Junior High School in District Jagoi Babang Bengkayang Regency to recruit Honorary Teachers or Teachers Not Permanent due to the condition of Elementary School and Junior High School in Jagoi Babang Sub-district of Bengkayang Regency is short of teachers, so inevitably the solution is by recruiting Master Honorary Teachers or Non-Permanent Teachers in order to support the teaching and learning process. In this research, it is recommended that the Government review the provisions that prohibit the appointment of honorary staff, especially Teachers of Honorary Teachers or Non-Permanent Teachers, considering that many schools are short of teachers; and There needs to be a revision to the provisions of Article 8 of Government Regulation Number 48 Year 2005 concerning the Appointment of Honorary Staffs to Candidate Civil Servants, in view of the need for Teachers of Honorary Teachers or Non-Permanent Teachers is a very necessary school because in reality Indonesia is still short of teachers.Â Keywords: Â Policy, Recruitment, Teachers Honorary.